Marketing System of Goat Livestock in Maranata Traditional Market of Sigi Regency - Afandi, Afandi (AgriSains, 2021)
The goatâ€™s marketing is mostly dominated by marketing institutions that have large scale business. This study aims to find out the marketing system and the benefits gained from each marketing goat market in Maranata Traditional Market, Sigi Regency. The study was conducted from November to December 2016. The research used descriptive analysis with sampling, incidential method to goat farmer and exploratory method to marketing institution. The population in this study is the total number of goat farmer and marketing institutions that amounted to 30 respondents. Based on results of the research, the goat marketing system in Maranata Traditional Market has 2 models of goat marketing channels. The process of establishing prices and payment patterns for goats begins with the buyer assessing the livestock. The highest profit in marketing of lane II is Rp. 383,417/ ekor, because has a low marketing cost because it only markets its livestock in the market. The lowest institution is the marketing channel I that is Rp. 346.612/ tails.Â